La pensée feministe noire : savoir, conscience et politique de l'empowerment - Hill Collins, Patricia (Les éditions du remue-ménage, 2016)
Confrontées à une société sexiste et raciste qui leur impose des images stigmatisantes d’elles-mêmes, les femmes noires des États-Unis n’en ont pas moins une longue histoire de résistances. Dans cet essai incontournable enfin traduit en français, Patricia Hill Collins nous offre une synthèse impressionnante de cette tradition d’oppression et de militantisme. La pensée féministe noire puise autant dans la littérature, les récits de vie, l’histoire militante, la philosophie sociale et politique, la sociologie critique que dans la culture populaire. Elle nous incite à penser non seulement les oppressions enchevêtrées, mais aussi les luttes passées et à venir. Ce livre donne accès à un savoir profondément ancré dans l’expérience irréductible des Africaines-Américaines; un savoir essentiel pour qui se préoccupe de justice sociale et pour un féminisme véritablement inclusif.
Le Chapitre 5 "Le pouvoir de l’autodéfinition" a été donné en lecture au cours POL4212.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; com5170; cours; cycles supérieurs; discipline; fem1000; fem3300; fem7000; féminismes noirs; har4600; incontournable; intersectionnalité; justice sociale; militance; pol4212; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie; états-unis

Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."–Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
https://oxford-universitypressscholarship-com.proxy.bibliotheques.uqam.ca/view/10.1093/acprof:oso/9780198237907.001.0001/acprof-9780198237907
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie

Black feminist thought: Knowledge, consciousness, and the politics of empowerment - Hill Collins, Patricia (Routledge, 2000)
A revision of a hugely successful book; this is the 'bible' of contemporary black feminist thought and is widely cited and taught as a seminal text. Completely up-to-date with recent events, trends in popular culture, current events, and politics.
Première publication : 1990 Édition 10e anniversaire
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; discipline; féminismes noirs; incontournable; intersectionnalité; justice sociale; militance; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie; états-unis